Antibacterial and larvicidal potentials of Derris indica (Lamk.) Bennet. extractives (University Journal of Zoology, Rajshahi University, 2012)
Chloroform extracts of the fruit shell, leaves, root bark, root wood, seeds, stem bark and stem wood of Derris indica were tested for their antibacterial and larvicidal potentials. Except the seed extract all other extracts offered activity against 15 pathogenic bacteria. The fruit shell extract showed activity against B. cereus, S.-β- haemolyticus and S. typhi; the leaf extract against Klebsiella sp. only; the root bark against B. cereus, B. megaterium, B. subtilis, S. -β- haemolyticus, S. typhi, S. dysenteriae and S. sonnei; the root wood extract against B. sereus, B. megaterium, B. subtilis, S. -β- haemolyticus, S. typhi, S. dysenteriae, S. shiga, S. sonnei, Klebsiella sp. and P. aeruginosa; the stem bark extract against B. cereus, B. subtilis, S. -β- haemolyticus and S. sonnei and the stem wood extract against B. cereus, B. megaterium, B. subtilis, S. -β- haemolyticus, S. typhi and S. dysenteriae. According to the intensity of activity against the selected bacteria the D. indica extracts could be arranged in a descending order of root wood> root bark> stem wood> stem bark> fruit shell> leaf extract. The minimum inhibitory concentrations (MICs) of the chloroform extract of root wood of D. indica were 128 μg/ml against S. -β- haemolyticus, B. megaterium and S. dysenteriae and 64 μg/ml against B. cereus; for the stem wood extract 128 μg/ml against S. -β- haemolyticus, B. megaterium, B. cereus and B. subtilis, and 64 μg/ml against S. dysenteriae. The root bark, root wood, seed and stem wood extracts showed efficacy against the 3rd instar larvae of Musca domestica with LC50 values in a descending order of root wood (3615.92 ppm) > seed (5538.07 ppm) > stem wood (12139.40 ppm) > root bark (16721.24 ppm).   Key words: Chloroform extract; Derris indica; antibacterial and larvicidal activity. DOI: http://dx.doi.org/10.3329/ujzru.v29i1.9460 UJZRU 2010; 29(1): 17-22